Adverse drug reaction reporting in Australian hospitals - Nita, Yunita (Curtin University, 2002)
Adverse drug reactions (ADRs) are known to be a major cause of morbidity and mortality. However, only a small proportion are reported. An increase in the number and quality of reports by improving ADR reporting systems in hospitals, could improve patient outcomes and save healthcare costs. The first part of this project was to review the ADR reporting systems in Australian hospitals and to determine factors contributing to the ADR reporting rate. Data were collected by a postal, self-administered questionnaire. Questionnaires were sent to 299 chief pharmacists of Australian hospitals listed in the Society of Hospital Pharmacists of Australia (SHPA) directory. The response rate was 49.5%. Seventy seven (60%) hospitals had a formal hospital policy for ADR reporting and 110 (85.3%) hospitals targeted all drugs to be reported. ADR reporting rates to ADRAC in 2000 (ADR reports per patient admission) were between zero and 1.09% (median=0.02%) with 7.1% of hospitals having a reporting rate of zero. A centralised ADR system and the existence of an ADR policy was not associated with higher reporting rates. The next part of the project was a survey of 803 Western Australian (WA) doctors and 1323 Australian hospital pharmacists to evaluate involvement in, understanding of and reasons for reporting ADRs. A postal, self-administered, anonymous questionnaire was sent to doctors at two tertiary hospitals in Perth and three regional hospitals in WA. A similar questionnaire was sent to all hospital pharmacists listed in the membership list of SHPA, as well as non-SHPA members in WA. Response rates obtained for the WA doctors survey was 35% (n=277) and 43% (n=574) for hospital pharmacists. Sixty four percent of doctors and 96% of hospital pharmacists knew how to report ADRs within the hospital while 57% and 98% (respectively) knew how to report ADRs to ADRAC.Factors that would encourage respondents to report ADRs included serious reactions, unusual reactions, reaction to a new product and confidence in the diagnosis of the ADR. More than 70% of respondents agreed that an uncertain association between the ADR and the suspected drug, minor reactions and well known reactions were factors that would deter them from reporting ADRs. From a list of 14 hypothetical ADR questions, it was found that respondents were more likely to report serious and uncommon reactions. Finally, the incidence of cross-sensitivity between penicillin and other β-lactam antibiotics among patients experiencing penicillin allergy in Fremantle Hospital and Health Services (FHHS) was assessed, along with the appropriate documentation of penicillin allergy in the medical records. The study was a retrospective audit and review of medical records in FHHS (1994-2000). All medical records of patients experiencing penicillin allergy during admission, or causing admission to FHHS, (n=85) were reviewed and data on reactions to other β-lactams were recorded. The incidence of definite cross-sensitivity between penicillins and cephalosporins was 6%, consistent with the reported rate of cross-sensitivity. The documentation of penicillin allergy in the medical records was less than optimal, with alerts on 89% of medication charts and only 28% of medical records (front cover). Improvement in the documentation of ADRs in patients' medical records would likely decrease the risk of preventable adverse events.